Harvest age and planting density effects on yield and quality of two kenaf (Hibiscus cannabinus l.) Varieties for fibre and animal feed - Mohammad Yusoff, Masnira (2015)
Kenaf (Hibiscus cannabinus L.) has been identified as a viable alternative crop to replace tobacco in Malaysian agriculture in the 21st century. Kenaf can be utilized for multiple purposes, whether for industrial applications or for livestock feed. Much information on components of yield such as plant height and density, stalk and leaf yield and total biomass have been obtained for the variety V 36. However, information on the new variety, MHC 123 is lacking, especially the understanding on how the yield components are affected by plant density and age. As plant density usually has an interaction with variety and harvest age the study looked at these factors in factorial combinations. From this information the optimum age and planting density for production of feed and fibre can be determined. The study was comprised of two experiments, one looking at harvest age and the other one on planting density effect. The first experiment had four harvest age treatments (8, 12, 16 and 20 weeks after planting) and two varieties (MHC 123 and V 36) as the treatments. The results indicated that the most suitable harvesting age for forage for kenaf variety V 36 was at 8 weeks after planting (WAP) while for MHC 123 it was at 12 WAP. This is based on the low decline in crude protein content from 8 to 12 WAP in MHC 123 (18.9 to 17. 2 %) compared to the rapid decline for V 36 (21.7 to 11.3 %). In addition, acid detergent fibre content in MHC 123 increased slowly (31.7 to 36.9 %) but in V 36 it increased drastically (39.5 to 55.6 %) from 8 to 12 WAP. Dry matter yield also was higher at 12 WAP (11.2 t ha-1) compared with 8 WAP (8.5 t ha-1) for MHC 123. The harvesting age for fibre was based on biomass yield and fibre quality (tensile strength, water absorption, bast and core yield). The suitable harvesting age for MHC 123 and V 36 were at same age, 16 WAP. However, MHC 123 had greater biomass yield with 11.7 t ha-1 compared to V 36 which was 8.7 t ha-1. The tensile strength of the fibre from MHC 123 (101.7 MPa) was higher than that of V 36 (59.8 MPa). Fibre from MHC 123 absorbed less water (116%) compared to V 36 (124.3%). The bast yield was also higher in MHC 123 (3.4 t ha-1) compared to V 36 (3.3 t ha-1) In the second experiment, there were 3 treatment combinations: planting density,harvest age and variety in split-split plot design with 4 replications. Harvest age was set as the main plot, planting density as a sub plot and variety as a sub-sub plot. The suitable plant density for MHC 123 and V 36 for forage was at 666,700 plants ha-1.This was based on MHC 123 and V 36 having higher CP content and lower ADF content at planting density of 666,700 plants ha-1. Planting density of 444,400 plants ha-1 was the best for fibre production for MHC 123 and V 36. This was based from the finding that MHC 123 and V 36 were higher in dry matter yield, bast yield, core yield at density of 444,400 plants ha-1. The dry matter yield was significantly (p<0.05) higher at the lowest density, 444,400 plants ha-1 with 12.7 t ha-1, followed by decreasing dry matter yield of 11.5, 11.2 and 10.3 t ha-1 for plant density at 500,000, 571,500, and 666 700 plants ha-1 respectively. MHC 123 has a potential to replace V 36. The superiority of MHC 123 over V 36 includes the higher leaf yield, stem yield, number of leaf plot-1, leaf to stem ratio, leaf area index (LAI),number of day to flowering and bast yield. The result of this study indicated that optimum harvest age and planting density vary with the variety of kenaf.